POLICY COMMUNICATION IN THE IMPLEMENTATION OF SINGLE IDENTITY NUMBER (SIN) - Maksum Syahri Lubis; Zoraya Alfathin Rangkuti; Muhammad Yusran (OPINI: Journal of Communication and Social Science, 2025)
The implementation of the Single Identity Number (SIN) policy through the integration of the National Identity Number (NIK) with the Taxpayer Identification Number (NPWP) represents a strategic effort by the Indonesian government to reform public administration and strengthen tax governance. Despite its strong regulatory foundation, the implementation of this policy at the local level has not fully achieved its intended outcomes. This study aims to analyze policy communication in the implementation of SIN at the local level, using a case study of the Primary Tax Office (KPP Pratama) Medan Belawan. Employing a qualitative descriptive approach, data were collected through in-depth interviews, observation, and document analysis. The analytical framework is based on Charles O. Jones’ policy implementation model, which emphasizes organization, interpretation, and application. The findings reveal that policy communication has not been implemented optimally due to limited human resources, budget constraints, inconsistent communication practices, and differences in policy interpretation between implementers and target groups. This study highlights that effective, consistent, and well-coordinated policy communication is essential to ensure public understanding and participation in the implementation of SIN.